2012
DOI: 10.3892/ol.2012.665
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CYP1A1, GSTP1 and GSTM1 gene polymorphisms and lung cancer risk among smokers

Abstract: Abstract. Lung cancer is the leading cause of cancer mortality worldwide and tobacco smoking has been established as its biggest risk factor. Cigarette smoke contains several carcinogens. Most of them need to be activated by phase I enzymes, such as cytochrome P450 (CYP), while phase II enzymes, such as glutathione S-transferases are responsible for the detoxification of activated forms. The present study aimed to determine the role of CYP1A1, GSTP1 and GSTM1 gene polymorphisms in smoking-related lung cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… 7 Among smokers, previous studies have revealed associations between the genes GSTM1 , GSTT1 , and GSTP1 and higher ORs for lung cancer. 1 , 8 , 9 However, among never smokers a recent investigation found no significant association between single or combined genotypes of GSTM1 , GSTT1 , or GSTP1 and lung cancer risk. 10 Additionally, TP53 mutations have also been highlighted more frequently in lung carcinomas arising in smokers than in never smokers.…”
Section: Introductionmentioning
confidence: 96%
“… 7 Among smokers, previous studies have revealed associations between the genes GSTM1 , GSTT1 , and GSTP1 and higher ORs for lung cancer. 1 , 8 , 9 However, among never smokers a recent investigation found no significant association between single or combined genotypes of GSTM1 , GSTT1 , or GSTP1 and lung cancer risk. 10 Additionally, TP53 mutations have also been highlighted more frequently in lung carcinomas arising in smokers than in never smokers.…”
Section: Introductionmentioning
confidence: 96%
“…CYP1A1 gene polymorphisms have been studied in association with the occurrence of several cancers in different populations. In the Greek population, CYP1A1 T3801C (*2A allele or MspI) polymorphism was not associated with smoking-related lung cancer risk in a study that included 100 patients with histologically or cytologically documented advanced lung cancer [94] or with the development of cervical intraepithelial neoplasia, in a study in 166 women with history of cervical intraepithelial neoplasia [95]. Similarly, CYP1A1*2A allele was not associated with breast cancer risk in a study in 207 female breast cancer patients [96].…”
Section: Cyp1a2mentioning
confidence: 88%
“…Lung cancer is the leading cause of cancer death worldwide. 1 , 2 There are more than 10 million deaths from lung cancer every year, largely because of the lack of effective early diagnosis and treatment. Despite improvements in the availability and sophistication of lung cancer treatment regimens, such as radiotherapy, chemotherapy, and surgery, the 5-year survival rate remains only 15% and has not increased significantly over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%